Orchestrating the Ocean Using a National Ocean Policy: The Case of the Solomon Islands - Hills, Jeremy M.; Lajaunie, Claire; Maharaj, Payal N.; Mazzega, Pierre (Frontiers in Marine Science, 2021)
Oceans are governed by multiple policies at international, regional and national levels. National level policies have traditionally been sector-based, covering fisheries, tourism, environment etc. Recently more integrated and holistic National Ocean Policies (NOP) have been promulgated. The Pacific Ocean also has well-developed regional ocean-related policies spanning decades. The work presented here uses lexicometric analysis to map the interlinkages between regional and national policies to determine if they are evolving synergistically. Focusing on the Solomon Islands, due to its reliance on the ocean and producing a NOP in 2018, 13,622 expressions were extracted from the corpus of 8 national and 10 regional ocean-related policies. Network analysis displayed limited differentiation between the NOP, national sector-based policies and regional policies. Clustering of policies showed progressive splitting of policies from a single cluster, rather than by formation of a number of separate clusters. This behaviour reflects the thematic interlocking of policies: all share many themes, and the more integrative policies add a few additional sectoral themes. The themes rarely addressed in the corpus include energy, agriculture, pollution and education. The NOP was predominantly built on existing national or regional policies and their main themes rather than setting a new direction in ocean governance. The benefit of the NOP may be less about its content itself, but the creation of allied cross-ministerial architecture. With the intense pressure on the oceans and its resources in present times, there will be a growing need for more substantive policy evolution.